IgG4 autoantibodies against muscle-specific kinase undergo Fab-arm exchange in myasthenia gravis patients. (February 2017) - Koneczny, Inga; Stevens, Jo A.A.; De Rosa, Anna; Huda, Saif; Huijbers, Maartje G.; Saxena, Abhishek; Maestri, Michelangelo; Lazaridis, Konstantinos; Zisimopoulou, Paraskevi; Tzartos, Socrates; Verschuuren, Jan; van der Maarel, Silvère M.; et al.
Abstract: Autoimmunity mediated by IgG4 subclass autoantibodies is an expanding field of research. Due to their structural characteristics a key feature of IgG4 antibodies is the ability to exchange Fab-arms with other, unrelated, IgG4 molecules, making the IgG4 molecule potentially monovalent for the specific antigen. However, whether those disease-associated antigen-specific IgG4 are mono- or divalent for their antigens is unknown. Myasthenia gravis (MG) with antibodies to muscle specific kinase (MuSK-MG) is a well-recognized disease in which the predominant pathogenic IgG4 antibody binds to extracellular epitopes on MuSK at the neuromuscular junction; this inhibits a pathway that clusters the acetylcholine (neurotransmitter) receptors and leads to failure of neuromuscular transmission. In vitro Fab-arm exchange-inducing conditions were applied to MuSK antibodies in sera, purified IgG4 and IgG1-3 sub-fractions. Solid-phase cross-linking assays were established to determine the extent of pre-existing and inducible Fab-arm exchange. Functional effects of the resulting populations of IgG4 antibodies were determined by measuring inhibition of agrin-induced AChR clustering in C2C12 cells. To confirm the results, κ/κ, λ/λ and hybrid κ/λ IgG4s were isolated and tested for MuSK antibodies. At least fifty percent of patients had IgG4, but not IgG1-3, MuSK antibodies that could undergo Fab-arm exchange in vitro under reducing conditions. Also MuSK antibodies were found in vivo that were divalent (monospecific for MuSK). Fab-arm exchange with normal human IgG4 did not prevent the inhibitory effect of serum derived MuSK antibodies on AChR clustering in C2C12 mouse myotubes. The results suggest that a considerable proportion of MuSK IgG4 could already be Fab-arm exchanged in vivo . This was confirmed by isolating endogenous IgG4 MuSK antibodies containing both κ and λ light chains, i.e. hybrid IgG4 molecules. These new findings demonstrate that Fab-arm exchanged antibodies are pathogenic. Highlights: MuSK autoantibodies can be induced to exchange Fab-arms in vitro . Fab-arm exchange is exclusive for the IgG4 subclass. Most MuSK autoantibodies are bispecific in vivo . Fab-arm exchange with normal IgG4 does not reduce pathogenicity in vitro . Monovalent MuSK antibodies are sufficient to cause disease.